2021
DOI: 10.1063/5.0045355
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of spatial resolution by tilt correction in near-field scanning microwave microscopy

Abstract: The limitation of mechanical manufacturing will result in a small tilt angle of the sample stage in the horizontal direction, which decreases the spatial resolution of imaging in near-field scanning microwave microscopy (NSMM). In this paper, we focus on the tilt correction and improve the spatial resolution of the NSMM image. The results of electromagnetic simulation and line scan measurement demonstrate the critical parameters affecting the sensitivity of NSMM, such as the length of the probe extending out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The central resonate frequency with the specimen compared with its no-load state. The frequency variation can help adjust the tip-sample distance to an appropriate distance [30], and it has potential application in other soft materials like biological cells [33]. Each concave in these figures represents the samples of specific molarities as solutions of different molarities have different electromagnetic parameters.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The central resonate frequency with the specimen compared with its no-load state. The frequency variation can help adjust the tip-sample distance to an appropriate distance [30], and it has potential application in other soft materials like biological cells [33]. Each concave in these figures represents the samples of specific molarities as solutions of different molarities have different electromagnetic parameters.…”
Section: Results and Analysismentioning
confidence: 99%
“…Compared with other types of resonators like planar resonators [31,32], our homemade λ/4 coaxial cylindrical resonator together with x-y-z motor stage shows the ability to obtain threedimensional images of electromagnetic properties of the specimen with higher resolution. Its spatial resolution can achieve 2 µm [30]. Through the lines, the resonator is connected to a vector network analyzer (VNA, Agilent Tech- -nologies E5062A).…”
Section: B Experimental Configurationmentioning
confidence: 99%
“…Zhang et al [ 8 ] reported a method that can correct the skewing and denoising of SMM images, significantly improving the spatial resolution of the images. They detected and obtained parametric images of f r , S 11 , and Q of the veins of leaves, as illustrated in Figure 16 .…”
Section: Recent Developments In Scanning Microwave Microscopymentioning
confidence: 99%
“… An enhanced grid contour image and f r parameter image of a copper film after tilt correction [ 8 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation